张先词用典研究 - 蒋, 瑀宸 (2023)
作为中国古典文学的重要组成部分，宋词的历史地位不可谓不高。用典，是本着一定的修辞目的，在自己作品中引用前人作品或故事的手法。宋词中用典的现象比比皆是，宋朝诸多词人也善于用典。本文所研究的词人张先，是北宋有名的长寿词人，其用典的形式多样、用典的内容丰富。“用典”修辞手法造就张先词清丽词风、奠定张先在北宋承前启后的文学地位，为北宋词坛做出了重要贡献。因此，本文通过整理张先词中的典故内容，归纳张先词中的典故类型，探究用典手法，了解用典为张先词风格的确立带来了怎样的影响。 本文涵盖了绪论、正文、结语三个部分的内容。第一章绪论主要说明本文的研究对象，总结出近年来张先研究以及用典研究领域取得的主要成果，并说明本文将如何展开研究。第二章介绍张先的生平；探究张先词中的典故主要包含哪些文体的内容以及主要借鉴哪些文人的作品或故事，并制成表格附录于文后。第三章主要分析张先使用典故的原因及类别，并以诗典举例说明。第四章概括用典手法为张先词带来了怎样的风格内涵。结语总结本文的研究内容，分析张先的影响力。As an important part of Chinese classical literature, Song Ci has a significant role in the history. Using allusion is one of the rhetorical methodsthat is quoting the previous works or stories in one’s own writing. In SongDynasty, numerous of Ci poets were proficient in allusion. Due to this phenomenon, the usage of allusions in the Ci poetry is commonly seen. ZhangXian, the Ci poet studied in this dissertation, is a famous longevity poet intheNorthern Song Dynasty. His Ci poetry allusions are diverse in formandrichincontent. The rhetorical technique of "allusion" created a clear and beautiful style of Zhang Xian's Ci poetry, established his literary position as a linkbetween the past and the future in the Northern Song Dynasty, and made important contributions to the literary world of the Northern Song Dynasty.Inorder to understand how the use of allusions affects the establishment of thestyle of Zhang Xian's Ci poetry style, this dissertation organizes the content of allusions involved in Zhang Xian's Ci poetry, summarizes the types of theseallusions, and explores the techniques of using allusions. This dissertation covers three parts: introduction, contents and conclusion. The first chapter is the introduction, which mainly describes the researchobject of this dissertation, summarizes the main achievements of ZhangXian's research and the research field of allusions in recent years, and explains howthis dissertation will carry out the research. The second chapter introduces Zhang Xian's life; To explore what literary styles are mainly included intheallusions in Zhang Xian's Ci poetry and what literary works or stories are mainly used for reference, and make an appendix table and append it at theback of dissertation text. The third chapter mainly analyzes the reasons andcategories of Zhang Xian's use of allusions, and illustrates themwith examplesof poems. The fourth chapter summarizes the style connotation of ZhangXian's words brought by using allusions. The conclusion summarizes the research content of this paper and analyzes the influence of Zhang Xian.